In vitro aging alters the gene expression and secretome composition of canine adipose-derived mesenchymal stem cells - Prišlin, Marina; Butorac, Ana; Bertoša, Rea; Kunić, Valentina; Ljolje, Ivana; Kostešić, Petar; Vlahović, Dunja; Naletilić, Šimun; Turk, Nenad; Brnić, Dragan (Frontiers in Veterinary Science, 2024)
Canine adipose-derived mesenchymal stem cells (cAD-MSCs) hold therapeutic promise due to their regenerative potential, particularly within their secretome. However, concerns arise regarding the impact of in vitro cultivation necessitated for storing therapeutic doses, prompting this study to comprehensively explore the impact of in vitro aging on gene expression and secretome composition. The study involved collecting abdominal adipose tissue samples from nine healthy female dogs, from which cAD-MSCs were extracted and cultured.Stem cells were validated through trilineage differentiation assays and flow cytometry immunophenotyping. Gene expression profiling using RT-qPCR array, and cAD-MSCs secretome LC-MS/MS analysis, were conducted at passages 3 and 6 to reveal gene expression and protein composition alterations during in vitro culture. The results demonstrate that the gene expression and secretome composition of cAD-MSCs were impacted by in vitro aging. Among many alterations in gene expression between two passages, two significant downregulations were noted in the MSC-associated PTPRC and IL10 genes. While the majority of proteins and their functional characteristics were shared between passages, the influence of cell aging on secretome composition is highlighted by 10% of proteins being distinctively expressed in each passage, along with 21 significant up-and downregulations. The functional attributes of proteins detected in passage 3 demonstrated a greater inclination towards supporting the regenerative capacity of cAD-MSCs. Moreover, proteins in passage 6 exhibited a noteworthy correlation with the blood coagulation pathway, suggesting an elevated likelihood of coagulation events. To the best of our knowledge, this study presents the first original perspective on the changes in secretome composition that occur when cAD-MSCs age in vitro.Furthermore, it contributes to broadening the currently restricted knowledge base concerning the secretome of cAD-MSCs. In conclusion, our findings show that the regenerative potential of cAD-MSCs, as well as their secretome, may be compromised by in vitro aging. Therefore, our study suggests a preference for earlier passages when considering these cells for therapeutic applications.